A multi-scale corrosion fatigue damage model of high-strength bridge wires. (June 2020) - Fan, Chen; Li, Zhaoxia; Wang, Ying
Cables are the most sensitive components in cable-supported bridges, and the failure of cables is usually caused by the degradation of mechanical properties of internal wires. Based on Faraday's law and the rates of microcrack initiation and propagation, a multi-scale corrosion fatigue damage model was developed to describe the damage evolution in the stages of pit growth and microcrack propagation. The accuracy and effectiveness of this damage model were also verified through the experimental data of corrosive fatigue life of high-strength bridge wires. The result shows that this damage model can describe the multi-scale corrosion fatigue damage evolution process of high-strength bridge wires reasonably and effectively, which provides a new way to better understand the trans-scale damage evolution mechanism during the corrosion fatigue process of high-strength bridge wires.